Designing a gamified approach for digital design education aligned with Education 4.0 - Cal Y. Mayor-Peña, Francisco; Barrera-Animas, Ari Y.; Escobar-Castillejos, Daisy; Noguez, Julieta; Escobar-Castillejos, David (Frontiers in Education, 2024)
IntroductionGamification integrates game-like elements, such as points, badges, and leaderboards, into the educational process. This study examines the influence of a gamified approach on improving graphic design education. By implementing this methodology, we aim to create a more dynamic learning environment that could lead to better academic outcomes.MethodsA quasi-experimental design was employed to compare students' average grades and academic achievements using the gamified technique with those taught using conventional methods. Thirty-two students participated in the study, with these students enrolled in three different terms. Data collection involved tracking students' grades, participation, and completion rates of gamified activities.ResultsParticipants in the August—December 2023 semester (Experimental 2 group) who experienced the gamified approach with the proposed platform showed significant improvement, with a p-value of 0.033, compared to those in the August—December 2022 semester (Control group), which used only conventional approaches. Furthermore, better learning outcomes were obtained when the Experimental 2 group was compared with the January-May 2023 semester (Experimental 1 group), which used only the gamification methodology (p-value = 0.025). Additionally, out of 15 students in the Experimental 2 group, 10 achieved certification in Adobe Illustrator and 13 in Photoshop, suggesting that gamification elements applied through a digital platform can improve academic performance and enhance students' practical skills and readiness for professional challenges in graphic design.DiscussionResults indicate that the gamified methodology can improve learning outcomes. Nevertheless, the proposed approach also has limitations and areas for improvement. Manual data capture, integration with external tools, the amount of teachers applying the approach, and the sample size of participants are limitations of the study that could have affected the accuracy of the results. Future work will focus on developing a proprietary platform that integrates course content and automates the tracking system to improve efficiency and accuracy. Moreover, a subsequent study will include a larger sample of students and professors to validate the present study's findings.